Beyond Normative Frameworks: The Pesantren Model as a Practical Blueprint for Taxonomy of Rehabilitation in Prisons - Musaddad, Anwar; Santosa, Agus Dwi; Dariyanto; Musoffa, Moch. Yusron; Utami, Pratiwi Tri (LETIGES, 2026)
This study addresses a critical gap in the literature by systematically assessing the practical implementation of Islamic education for inmates, moving beyond the conventional focus on merely documenting Islam in prisons. Drawing on Fousberg and Douglas's rehabilitation taxonomy, which conceptualises the progressive steps of inmate rehabilitation, this research explicitly examines the transition from theoretical classification to concrete implementation. The study shows how the Pesantren model actively operationalises this normative framework into practical moral and social rehabilitation. This study employed a qualitative multiple-case study design conducted in Class II prisons across Kediri, Jombang, Blitar, and Nganjuk, East Java, Indonesia. Using purposive sampling, researchers selected 45 participants, including inmates, prison officers, and Islamic educators. Researchers collected data through semistructured interviews, direct observations, and documentation. Methodological and source triangulation were applied to ensure the trustworthiness of the data, while thematic analysis was utilised to identify and categorise implementation patterns of Islamic education in inmate rehabilitation. The originality of this study lies in offering a novel, replicable framework that transforms abstract rehabilitation concepts into actionable, real-world educational interventions. By doing so, this model contributes to the broader objective of Sustainable Development Goal 4, with the Pesantren model promoting inclusive and equitable quality education within prisons. The study's limitations prominently include its focus on moderate-security prisons and the specific context of Muslim-majority countries. Therefore, researchers need to conduct further studies to evaluate how these findings can apply to high-risk facilities and nations with different religious demographics.